2016
DOI: 10.18632/oncotarget.14262
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin induces autophagy-mediated c-FLIPL degradation and leads to apoptosis in human non-small cell lung cancer cells

Abstract: Cordycepin, a main active composition extracted from Cordyceps militaris, has been reported to exert anti-tumor activity in a broad spectrum of cancer types. However, the function of cordycepin on human non-small cell lung cancer cells is still obscure. Our present work showed that cordycepin inhibited cell growth by inducing apoptosis and autophagy in human NSCLC cells. Further study revealed that cordycepin triggered extrinsic apoptosis associated with down-regulation of c-FLIPL which suppresses the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
(27 reference statements)
0
17
1
Order By: Relevance
“…These results indicate that such reductions of anti-apoptotic proteins may explain, at least in part, why CQ promoted TRAIL-induced apoptosis. However, our results contradict those of other reports indicating that activation of drug-mediated autophagy promotes the degradation of cFLIP and other anti-apoptotic proteins, triggering apoptosis and/or increasing TRAIL-sensitivity [ 35 37 ]. The cited studies used human non-small-cell lung cancer cells, whereas we utilized human pancreatic cancer cell lines.…”
Section: Discussioncontrasting
confidence: 99%
“…These results indicate that such reductions of anti-apoptotic proteins may explain, at least in part, why CQ promoted TRAIL-induced apoptosis. However, our results contradict those of other reports indicating that activation of drug-mediated autophagy promotes the degradation of cFLIP and other anti-apoptotic proteins, triggering apoptosis and/or increasing TRAIL-sensitivity [ 35 37 ]. The cited studies used human non-small-cell lung cancer cells, whereas we utilized human pancreatic cancer cell lines.…”
Section: Discussioncontrasting
confidence: 99%
“…In the FHD group, there were no significant mean changes in Biochemical parameter between baseline and post-treatment [49] [50]. …”
Section: Safety Assessmentmentioning
confidence: 76%
“…Traditional Chinese medicine is one of them for complementary and alternative therapy. Cordycepin, an active compound extracted from one Traditional Chinese medical herb, Cordyceps militaris, has been studied to treat many cancers including lung cancer (50), ovarian cancer (46), leukemia (30), breast cancer (47), brain cancer (19), colon cancer (27), liver cancer (25), and so on (33). Recently, some efforts have been done to investigate the po- PTEN/PI3K/Akt signaling pathway is an important pathway regulated by microRNA-21 (7).…”
Section: Discussionmentioning
confidence: 99%
“…Development of neo-adjuvant therapy is still in a demand at present. Cordycepin is a main active composition extracted from Cordyceps militaris and has been reported to harbor anti-tumor activity in a broad spectrum of cancer types, including lung cancer (50), ovarian cancer (46), leukemia (30), breast cancer (47), and so on (33). Two recent reports firstly demonstrated that cordycepin could induce apoptosis in renal cell carcinoma through Erk-JNK signaling pathway (20,48) and indicated the potential application of cordycepin in treating renal cell carcinoma.…”
mentioning
confidence: 99%